Obtenção e caracterização de nanocompósitos TiO2 –OGR para aplicações fotocatalíticas - Bruno de Souza Gonçalves (2019)
Organic dyes are widely used in many industrial fields and are responsible for the production of large volumes of residues every year. When present in rivers and seas, they change the water color and also inhibit the sunlight penetration. As a consequence, the photosynthetic activity of plants is impaired, compromising the survival of many living organism. Because of this scenario, the degradation of organic dyes shows a great scientific and environmental importance. Several works available in the literature report that titania (TiO2) exhibits an expressive catalytic activity. Graphene has been used for preparing composites with TiO2 due to its high specific surface area and electrical conductivity. In fact, it has been reported that TiO2-reduced graphene oxide (RGO) composites usually show a significant photocatalytic activity, which is largely associated with an efficient transference of charge carriers between TiO2 and RGO. In this work it was prepared TiO2 nanoparticles and TiO2-RGO nanocomposites using either ethanol (EtOH) or isopropyl alcohol (IPA) as solvent. The photocatalytic activity of the samples prepared in this study was evaluated by assessing the degradation rate of methylene blue (MB) under ultraviolet (UV) irradiation. It was observed that in a general way, samples prepared with IPA displayed larger specific surface areas than those obtained with EtOH. It is reported in the literature that the use of branched-chain alcohols like IPA gives rise to particles with a larger density of surface defects than straight-chain alcohols like EtOH. It was prepared composites showing RGO loadings ranging from 0.5 to 20 wt %. We observed that the samples with the highest photocatalytic activities were those ones obtained with a 1 wt % RGO concentration. It is believed that the higher the RGO loading in the prepared materials, the more pronounced is the agglomeration of RGO nanosheets, which may prevent the incident light to reach the TiO2 nanoparticles. This behavior decreases the photocatalitic activity of the TiO2-RGO composite.